The lost dinosaurs the astonishing discovery of the world's largest prehistoric nesting ground - Chiappe, Luis M.; Dingus, Lowell (Abacus, an imprint of Time Warner Books UK, 2002)
"Walking on Eggs is the inside story behind one of the most significant paleontological discoveries in history. In November 1997, Luis M. Chiappe and Lowell Dingus led an elite team of paleontologists and geologists into the rugged and desolate badlands of Argentina. Unsure of what they would find, Chiappe and Dingus knew that this region had produced many spectacular specimens of dinosaurs and fossil birds over the last century. Nothing could have prepared them, however, for the headline-grabbing discovery they were about to make: a massive dinosaur nesting ground covering more than a square mile and littered with tens of thousands of large, unhatched dinosaur eggs. Containing the first fossils of embryonic dinosaur skin ever found, the eggs gave rise to a host of mysteries. What species laid the eggs, and when? How were they preserved? And most intriguingly, what ancient catastrophe - deeply rooted more than 70 million years in the past - prevented them from hatching?"